THE MAKKAH ROUTE INITIATIVE AND ITS IMPACT ON THE EFFECTIVENESS OF HAJJ SERVICES IN INDONESIA: A CASE STUDY OF SAUDI ARABIA'S HAJJ POLICY - Mohamad Rifai; Agung Permadi (Budi Luhur Journal of Strategic & Global Studies, 2026)
Abstract: This study aims to analyze how the Makkah Route Initiative (MRI) functions as an instrument of Saudi Arabia’s soft power and how improvements in Hajj service effectiveness contribute to the construction of Saudi Arabia’s international image among Indonesian pilgrims. Using a descriptive qualitative case-study approach, the research examines MRI implementation in Indonesia during the 2024 Hajj season through official reports, policy documents, and academic literature. Service effectiveness is assessed through indicators of processing speed, reduction of waiting time, administrative simplification, logistical efficiency, and pilgrim convenience. The findings indicate that MRI served 128,949 Indonesian pilgrims and reduced immigration processing time to approximately 50 seconds per pilgrim. Through Nye’s soft power perspective, MRI converts administrative and technological capacity into attraction, legitimacy, and positive perceptions of Saudi Arabia as a modern and human-centered administrator of Hajj services. The study recommends strengthening inter-institutional coordination and digital infrastructure to sustain service quality and reinforce the long-term soft power benefits of the initiative. Abstrak: Studi ini bertujuan untuk menganalisis bagaimana Makkah Route Initiative (MRI) berfungsi sebagai instrumen soft power Arab Saudi dan bagaimana perbaikan dalam efektivitas layanan Haji berkontribusi pada pembangunan citra internasional Arab Saudi di kalangan jemaah haji Indonesia.  Menggunakan pendekatan studi kasus kualitatif deskriptif, penelitian ini meneliti pelaksanaan MRI di Indonesia selama musim Haji 2024 melalui laporan resmi, dokumen kebijakan, dan literatur akademis.  Efektivitas layanan dinilai melalui indikator kecepatan pemrosesan, pengurangan waktu tunggu, penyederhanaan administratif, efisiensi logistik, dan kenyamanan jemaah.  Temuan menunjukkan bahwa MRI melayani 128.949 jemaah haji Indonesia dan mengurangi waktu pemrosesan imigrasi menjadi sekitar 50 detik per jemaah.  Melalui perspektif kekuatan lembut Nye, MRI mengubah kapasitas administratif dan teknologi menjadi daya tarik, legitimasi, dan persepsi positif terhadap Arab Saudi sebagai administrator layanan Haji yang modern dan berpusat pada manusia.  Studi ini merekomendasikan penguatan koordinasi antar lembaga dan infrastruktur digital untuk mempertahankan kualitas layanan dan memperkuat manfaat soft power jangka panjang dari inisiatif tersebut.